2020
DOI: 10.1155/2020/3580491
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Stepped Planing Hulls in Finding an Optimized Step Location and Analysis of Its Porpoising Phenomenon

Abstract: Stability of a high-speed craft is an essential matter, and porpoising is one of the most critical instabilities that could occur in some planing hulls due to inappropriate design. In this paper, the porpoising phenomenon and variation of step location yielding resistance reduction are studied through experimental and numerical methods. The investigated models include a single-step model and a nonstep model with the same general shape, but with different step location. The nonstep model is previously tested, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The towing test results were extracted and processed, and Figure 5 plots the total resistance, trim angle, and sinkage of the schemes of the bare hull as functions of the volumetric Froude number Fn. In general, the porpoising of a monoplaning hull often arises at a speed no greater than Fn = 5 [19][20][21][22][23], while the conversion Froude number exceeded 7 in the current paper; this indicates that the planing trimaran showed excellent high-speed performance.…”
Section: Effects Of Longitudinal Position Of the Gravity Centermentioning
confidence: 82%
See 1 more Smart Citation
“…The towing test results were extracted and processed, and Figure 5 plots the total resistance, trim angle, and sinkage of the schemes of the bare hull as functions of the volumetric Froude number Fn. In general, the porpoising of a monoplaning hull often arises at a speed no greater than Fn = 5 [19][20][21][22][23], while the conversion Froude number exceeded 7 in the current paper; this indicates that the planing trimaran showed excellent high-speed performance.…”
Section: Effects Of Longitudinal Position Of the Gravity Centermentioning
confidence: 82%
“…Lu et al studied the coupling action of a stern flap and step on a monoplaning hull, both experimentally and numerically [7]. Sajedi and Ghadimi assumed the wetted surface area as a step height and location function, and by experimental and numerical investigation, the optimal layout and configuration of the step were discussed and extracted with the aim of minimizing the resistance [21]. Furthermore, a series of towing tests were carried out by Ghadimi et al, analyzing the hydrodynamic performance and effect of appendages such as wedges and steps on resistance and stability performance [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Sajedi and Ghadimi [28] also experimentally studied the singlestepped hull in the presence of irregular waves. Supported by these experimental data for single-stepped hulls, Sajedi and Ghadimi [34] tried to fgure out the best location of a transverse step by examining ten diferent steps' longitudinal locations in a numerical efort.…”
Section: Introductionmentioning
confidence: 99%
“…Tey found that the simultaneous use of stern wedges and transverse steps could improve the vessel's undesirable performance prior to planing regime, which is one of the challenges in planing hull design. Tese extensive data [9,28,29,[31][32][33][34][35][36][37] for diferent confgurations of a single parent model present a unique opportunity to realize how diferent confgurations of step and wedge could afect a planing hull's performance.…”
Section: Introductionmentioning
confidence: 99%
“…Caterino and Mancini 23 attempted to find an optimized unwetted aft area behind the steps of stepped hulls, with the aim of drag reduction and dynamic stability improvement. Finding the optimized step location was also pursued by Sajedi and Ghadimi 24 who attempted to obtain the least resistance. Their measurements showed that total resistance of the vessels is more dependent on the longitudinal step location than the sailing speed.…”
Section: Introductionmentioning
confidence: 99%